Discordance of serological and sonographic markers for Hashimoto's thyroiditis with gold standard histopathology. Issue 5 (November 2019) - Guan, Haixia; de Morais, Nathalie Silva; Stuart, Jessica; Ahmadi, Sara; Marqusee, Ellen; Kim, Mathew I; Alexander, Erik K.
Abstract : Objective: To investigate the concordance of serologic and sonographic evidence of Hashimoto's thyroiditis with its gold standard histopathologic identification. Design: We performed a retrospective analysis on a cohort of 825 consecutive patients in whom TPOAb and thyroid ultrasound were performed, and in whom thyroid nodule evaluation led to surgical and histopathologic analysis. The presence or absence of Hashimoto's thyroiditis on histopathology was correlated with serologic and sonographic markers. We further assessed the impact of low versus high titers of TPOAb upon this concordance. Results: Of 825 patients, 277 (33.5%) had histologic confirmation of Hashimoto's thyroiditis, 235 patients (28.4%) had elevated serum levels of TPOAb, and 197 (23.8%) had sonographic evidence of diffuse heterogeneity. Of those with histopathologic evidence, only 64% had elevated TPOAb (sensitivity: 63.9%; specificity: 89.4%), while only 49% were sonographically diffusely heterogeneous (sensitivity: 49.1%; specificity: 88.9%). A subset of only 102 of 277 (37%) with histologically proven Hashimoto's thyroiditis was positive for both TPOAb and diffusely heterogeneous. Concordance analysis demonstrated that TPOAb and histopathology had higher agreement (κ = 0.55) than did ultrasound and histopathology (κ = 0.40) for the diagnosis of Hashimoto's thyroiditis. Higher titers of TPOAb correlated with a higher likelihood of Hashimoto's thyroiditis, with a best cutoff of 2.11-fold the upper normal level of TPOAb. Conclusion: Only moderate concordance exists between serological evidence of Hashimoto's thyroiditis and histopathologic findings, though it increases with higher TPOAb concentration. Diffuse heterogeneity on ultrasound is a less-sensitive diagnostic tool than elevated TPOAb.